Cardiometabolic responses to L-carnitine in obese women with knee osteoarthritis: a randomized, double-blind, placebo-controlled pilot study - Malek Mahdavi, Aida; Mahdavi, Reza; Kolahi, Sousan; Ebrahimzadeh Attari, Vahideh (Progress in Nutrition, 2018)
This study aimed to investigate cardiometabolic responses to L-carnitine in obese women with knee osteoarthritis (OA). In this randomized double-blind, placebo-controlled trial, 50 obese women with mild to moderate knee OA were randomly allocated into 2 groups to receive 750 mg/d L-carnitine or placebo for 8 weeks. Anthropometric indices, blood pressure and atherogenic indices were measured before and after the intervention. Only 48 patients (23 in the L-carnitine group and 25 in the placebo group) completed the study. L-carnitine resulted in significant reduction in hip circumference (115.15±6.19 vs 113.57±4.89) compared with baseline (P=0.013); whilst it didn’t change body mass index, waist circumference, waist to hip and waist to height ratios significantly (P>0.05). L-carnitine led to significant reduction in systolic blood pressure compared with placebo group, adjusted for baseline values (P=0.020). Atherogenic indices didn’t change significantly in both groups through the study (P>0.05). No significant differences were observed in anthropometric measures and atherogenic indices between two groups after adjusting for baseline values and covariates (P>0.05). In conclusion, L-carnitine did not lead to significant changes in obesity-associated parameters and atherogenic indices in women with knee OA. However, long-term studies with higher doses of L-carnitine are needed to explore its efficacy as an anti-obesity and anti-atherogenic agent in OA patients.